ผลกระทบของการใช้พอลิเมอร์ในการครีมหางน้ำยางธรรมชาติต่อคุณภาพน้ำทิ้ง - จุไรรัตน์ นิตยพัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
In this study, hydroxypropyl methylcellulose (HPMC) and hydroxypropyl cellulose (HPC) were used instead of concentrated sulfuric acid in the creaming process of skim natural rubber latex. The effluents from creaming process using HPMC and HPC as well as those with recovery of the polymer were compared to the use of concentrated sulfuric acid. In overall, the pollution of the effluent from creaming process was improved using recovered HPMC and HPC process. The effluent acidity, conductivity, sulfate ion, total kjeldahl nitrogen (TKN) and ammonia values were significantly lower but total dissolved solids (TDS), biochemical oxygen demand (BOD) and chemical oxygen demand (COD) were slightly higher. Moreover, the effluents retention time affected the pollution of the effluent from HPMC and HPC process as well as recovered HPMC and recovered HPC process. The acidity, total kjeldahl nitrogen (TKN), ammonia and Fat Oil and Grease (FOG) values of the effluent were decreased as increasing the effluent retention time. In contrast, suspended solids (SS), total dissolved solid (TDS), sulfate ion, sulfide as H2S, biochemical oxygen demand (BOD) and chemical oxygen demand (COD) were increased. However, the high values of BOD and COD were valuable for wastewater by anaerobic system.